2020
DOI: 10.1177/0896860820942628
|View full text |Cite
|
Sign up to set email alerts
|

Burden in primary family caregivers caring for uremic patients on maintenance peritoneal dialysis

Abstract: Background: Managing the burden of care for patients with chronic debilitating diseases is an important issue. Herein, we assessed the burden in primary family members caring for uremic patients on maintenance peritoneal dialysis. Methods: One hundred seventy caregivers and 170 patients were recruited. Self-perceived scoring along the Zarit Caregiver Burden Scale (ZCBS), World Health Organization Five-item Well-Being Index (WHO-5), and Warwick–Edinburgh Mental Well-being Scale (WEMWBS) were determined for care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 23 publications
0
25
1
1
Order By: Relevance
“…Of the included studies, 35 used a cross sectional design [5,[9][10][11][12] and three provided cross sectional data within other designs; one used a quasi-experimental design [46], one used a longitudinal design [47], and one a mixed method design [6]. Studies included in the review were completed in a variety of countries, including: seven in Turkey [11,[22][23][24]27,33,46], four in the USA [5,18,29,44], four in Iran [31,34,37,39], two in Brazil [25,26], two in Japan [34,41,43], two in Saudi Arabia [9,21], three in China [12,42,45], two in Nigeria [6,17], two in Jordan [16,19], two in India [32,35]; and a single study in Nepal [10], Canada [38], Pakistan [40], Greece [36], Spain [20], Singapore [47], Vietnam [30], and Indonesia…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the included studies, 35 used a cross sectional design [5,[9][10][11][12] and three provided cross sectional data within other designs; one used a quasi-experimental design [46], one used a longitudinal design [47], and one a mixed method design [6]. Studies included in the review were completed in a variety of countries, including: seven in Turkey [11,[22][23][24]27,33,46], four in the USA [5,18,29,44], four in Iran [31,34,37,39], two in Brazil [25,26], two in Japan [34,41,43], two in Saudi Arabia [9,21], three in China [12,42,45], two in Nigeria [6,17], two in Jordan [16,19], two in India [32,35]; and a single study in Nepal [10], Canada [38], Pakistan [40], Greece [36], Spain [20], Singapore [47], Vietnam [30], and Indonesia…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three studies reported moderate CB in the caregiver dialysis group and low CB in caregivers of RT patients [22,23,35]. Mild to moderate burden was reported in caregivers of patients receiving HD [12,17,33,40,42,43,45,47] and patients receiving PD [27]. One study reported mild to moderate CB in caregivers of patients receiving PD, HD, and RT [24].…”
Section: Level Of Cbmentioning
confidence: 99%
See 3 more Smart Citations